Dermoscopic features and follow‐up changes of acral melanocytic naevi in childhood and adolescence. (1st February 2014) - Fargnoli, M.C.; Suppa, M.; Micantonio, T.; Antonini, A.; Tambone, S.; Peris, K.
Summary: Background: The dermoscopic features of acral acquired melanocytic naevi have been extensively reported in the adult population. Little knowledge is available on acral naevi in childhood and adolescence. Objectives: Firstly, to characterize the frequency of dermoscopic features of acral naevi and their distribution according to age groups in children and adolescents; and secondly, to analyse the type and frequency of their dermoscopic changes over time. Methods: A retrospective evaluation of baseline and follow‐up dermoscopic images of acral naevi in Italian patients aged 0–18 years was carried out. Results: Dermoscopic images of 75 acral naevi (39 in children and 36 in adolescents) in 69 patients were evaluated. The parallel furrow was the most common pattern (71%), followed by the crista dotted pattern (21%). A difference in the distribution of global patterns was observed between children and adolescents ( P = 0·02). Combination patterns were detected in 32% of lesions, with association of the crista dotted and parallel furrow patterns in 62% of these. Follow‐up images were available for 31/75 acral naevi (41%), with a median follow‐up period of 32 months (range 4–85). Morphological variations during follow‐up were identified in 61% of lesions. Global changes involved mainly naevi with a baseline parallel furrow pattern, after a follow‐up of > 30 months. A decrease of local criteria during follow‐up was observed in 48% of lesions. Conclusions: Parallel furrow and crista dotted patterns, either alone or in combination, were the most common dermoscopic patterns. Morphological changes during follow‐up were frequent, involving mainly the parallel furrow pattern with a decrease of local criteria. Recognition of the dermoscopic features of acral naevi of children and adolescents is important to improve proper management and reduce the number of unnecessary excisions.